2010
DOI: 10.1177/147470491000800304
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between Perceiver and Wearer Effects in Clothing Color-Associated Attributions

Abstract: Recent studies have noted positive effects of red clothing on success in competitive sports, perhaps arising from an evolutionary predisposition to associate the color red with dominance status. Red may also enhance judgments of women's attractiveness by men, perhaps through a similar association with fertility. Here we extend these studies by investigating attractiveness judgments of both sexes and by contrasting attributions based on six different colors. Furthermore, by photographing targets repeatedly in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
141
5
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(156 citation statements)
references
References 37 publications
(62 reference statements)
9
141
5
1
Order By: Relevance
“…Even if the effect occurs in real life, we cannot conclude that it is based on the same processes as the effect found here in the lab. Wearing formal apparel, for instance, might change the wearer's feeling and manner, which will further influence the way observers perceive him ("wearer effect"; with regard to color-associated impacts a wearer effect was shown by Roberts, Owen, & Havlicek, 2010). Using static stimuli with an a posteriori color manipulation, as we did in the present research, does not allow for the reproduction of such processes; the effect of apparel style that we found in the lab must ipso facto be based on something else.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the effect occurs in real life, we cannot conclude that it is based on the same processes as the effect found here in the lab. Wearing formal apparel, for instance, might change the wearer's feeling and manner, which will further influence the way observers perceive him ("wearer effect"; with regard to color-associated impacts a wearer effect was shown by Roberts, Owen, & Havlicek, 2010). Using static stimuli with an a posteriori color manipulation, as we did in the present research, does not allow for the reproduction of such processes; the effect of apparel style that we found in the lab must ipso facto be based on something else.…”
Section: Discussionmentioning
confidence: 99%
“…Some work exists that examines the effect of red on women's perceptions of men's attractiveness (Elliot et al, 2010;Roberts et al, 2010), although research in this direction is less common, and a parallel effect is not always observed Hesslinger, Goldbach, & Carbon, 2015) 1 . The effect of red on ratings of women's attractiveness may be more robust because ratings of men's attractiveness are more likely to be moderated by the targets' emotion expression, women's conception risk, and perceptions of aggression or anger (Buechner, Maier, Lichtenfeld, & Elliot, 2015;Prokop, Pazda, & Elliot, 2015;Stephen, Oldham, Perrett, & Barton, 2012;Young, Elliot, Feltman, & Ambady, 2013).…”
Section: Facial Redness Increases Men's Perceived Healthiness and Attmentioning
confidence: 99%
“…In birds, red leg bands enhance access to resources in male zebra finches [6], while rhesus macaques avoid red-wearing human experimenters [7]. In humans, several studies have shown that colour stimuli have similar effects on social perception [8,9] and behaviour such as the outcome of physical and virtual contests (see [10] for review). Being associated with or wearing red are also linked to higher heart rate, a greater pre-performance strength and higher testosterone levels [11,12].…”
Section: Introductionmentioning
confidence: 99%